Role of Transverse Cerebellar Diameter in Diagnosis of Asymmetrical Fetal Growth Restriction - Nasir Khan (Journal of Rawalpindi Medical College, 2013)
Background: To evaluate the accuracy of transcerebellar diameter and transcerebellar diameter /abdominal circumference ratio (TCD/AC) as independent predictor for asymmetrical fetal growth restriction Methods: In this observational study 30 high risk patients clinically assessed for suspected fetal growth restriction were included. Serial Ultrasound scans were done on these patients. Various biometric measurements with special emphasis on transverse cerebellar diameter / abdominal circumference ratio (TCD/AC) were taken. Sonologically estimated fetal weight (EFW) was calculated and fetuses with estimated fetal weight less than 10th percentile were then serially observed till birth. Diagnosis was confirmed at birth. Results: Fourteen patients were diagnosed by ultrasound of having asymmetrical fetal growth restriction which was later confirmed after birth by neonatal birth weight, having less than 10th percentile. Prevalence of asymmetrical growth restriction was 53.33%.Four patients who were diagnosed antenatally by ultrasound having asymmetrical growth restriction did not have fetal growth restriction at birth. Two patients who were diagnosed as having normally growing fetuses sonologically turned out to be having asymmetrical growth restriction on birth. The best cut off value of the TCD/AC ratio for predicting fetal growth restriction was 0.1603. Raised TCD/AC ratio was observed in 15 patients out of 30 (50%). Two patients were found to have placenta previa (6.67%) and 8 (26.67%) with inadequate liquor volume having amniotic fluid index (AFI) less than 8. Conclusions: Transverse cerebellar diameter and its ratio with abdominal circumference is a reliable sonological predictor in antenatal diagnosis of asymmetrical fetal growth restriction (brain-sparing type).